2007
DOI: 10.1080/14992020601002123
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MRI findings with traditional criteria in diagnosis of Pendred syndrome

Abstract: Pendred syndrome, defined as the constellation of goiter, sensori-neural hearing loss, and positive perchlorate discharge test, is the most frequent cause of congenital deafness. Newly introduced diagnostic approaches to the disease are rather expensive and complicated, therefore we evaluated the value of MRI as the sole, or adjunctive diagnostic approach, and compared it with the traditional ones. Presuming the classic triad as the gold standard, we compared MRI findings in six such defined patients with six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In one study, over 80% of familial cases of Pendred syndrome demonstrated structural malformations of the cochlea, identifiable by CT scan 12. Another study found MRI imaging to be 83.6% sensitive in detecting patients with Pendred syndrome 21. The Mondini malformation of the cochlea is not specific to Pendred syndrome, but is often present.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, over 80% of familial cases of Pendred syndrome demonstrated structural malformations of the cochlea, identifiable by CT scan 12. Another study found MRI imaging to be 83.6% sensitive in detecting patients with Pendred syndrome 21. The Mondini malformation of the cochlea is not specific to Pendred syndrome, but is often present.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstrated experimental fusion of imaging techniques used in this study offers useful methodology for detection and investigation of cochlear hypoplasia, vestibular dehiscence, partial or total semicircular canal aplasia, dysmorphogenesis and malformations of the vestibulo-cochlear systems in mutant mouse models that are associated with birth defects related to genetic inner ear disorders in humans, such as in Crouzon syndrome and Pendred syndrome and disorders of the vestibular system [ 19 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%